Produtos da química fina através da metátese de propenilbenzenos de origem vegetal empregando catalisadores rutênio-alquilideno - Alexandra Goncalves Santos (2017)
In this work new methodologies with technological potential for high value-added products were developed from biorenewable 1-propenylbenzenes, anethole, isoeugenol and isosafrol, available in abundance in Brazil. This development consisted in the application ofolefin metathesis using the second-generation Grubbs (GII), Umicore M2 (M2) and Hoveyda-Grubbs second generation (HGII) catalysts, in the transformation of these substrates into products of commercial interest for fine chemistry. Cross-metathesis of 1-propenylbenzenes with methyl acrylates and 2-ethylhexyl acrylates is a highly efficient route for the synthesis of cinnamates, compounds that absorb ultraviolet radiation, and ferulates, molecules with antioxidant, anti-inflammatory andanticancer properties. Using GII and M2 in these reactions, the yields obtained are limited by the decomposition of these catalysts by enolates formed due to the interaction of the tricyclohexylphosphine, dissociated from those in the initiation step, with the acrylates. A simple process of increasing the performance of GII and M2 to levels corresponding to themost active, but much more expensive, HGII is described; the execution of this reaction in the presence of poly(vinylphenols), promoters which can be separated from the reaction by performing a simple filtration.From the cross-metathesis reactions of the arylpropenes with 1,4-diacethoxybut-2-ene a procedure was developed for the synthesis of esters, compound that can be hydrolyzed for the production of alcohols: methoxycinnamic and coniferylic, products with potential application in industry chemistry. p-cymene, a biorenewable solvent, is an excellentalternative for replacing the highly dangerous solvent 1,2-dichloroethane in these reactions and cross-metathesis of 1-propenylbenzenes with acrylates. Using this solvent, it was possible to associate efficiency and sustainability in these reactions. Finally, using self-metathesis of 1-propenylbenzene was developed a sustainable procedure for the synthesis of stilbenes, substances with fluorescence, anti-inflammatory,anti-inflammatory, antitumor and cardioprotective properties, with very low amounts of GII and HGII, in reactions that occur instantly, without addition of solvents and without the need for heating.